Lima Pilar Ketahanan Keluarga Ustadz-Ustadzah Pesantren: Strategi Spiritual, Komunikatif, Edukatif, dan Sosial-Ekonomi di PPTI Al-Falah - Imamul Muttaqin; Tri Wahyu Hidayati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study aims to analyze the strategies employed by ustadz and ustadzah at Pondok Pesantren Tarbiyatul Islam (PPTI) Al-Falah in maintaining family resilience. The family, as the smallest unit in society, plays a crucial role in shaping individuals’ character, morality, and spirituality, particularly for those living in a pesantren environment characterized by intensive religious and educational activities. This research uses a qualitative method with a case study approach. Data were collected through interviews and observations involving married ustadz and ustadzah who reside within the pesantren environment. The results indicate that in building a household, conflicts are inevitable. Due to teaching responsibilities that often extend into the night, miscommunication may occur and potentially lead to domestic issues. Therefore, family resilience among ustadz and ustadzah at PPTI Al-Falah is developed through five main strategies: (1) spiritual strategies, (2) communicative strategies, (3) educational strategies, (4) social and environmental strategies, and (5) economic and time management strategies.